MENGEMBANGKAN DAN MEMFASILITASI SUDUT BACA KELAS UNTUK MENINGKATKAN MINAT BACA SISWA - Elisa Margareth Bawinto; Amelia Mooduto (Journal of Community Services on Multidisciplinary Sciences, 2025)
The reading interest of elementary school students in Indonesia is still relatively low, which has an impact on the quality of learning in the classroom. This project aims to develop and facilitate reading corners in the classroom as a strategy to increase students' interest and reading habits. The reading corners are designed with attractive and child-friendly visual designs, equipped with a varied collection of books, ranging from picture stories, fairy tales, educational comics to light reading in English. This project also involves class teachers as the main facilitators who integrate literacy activities into daily learning, such as reading together, sharing stories and independent reading. The main objectives of this project are to create a literate and enjoyable classroom environment, improve students' literacy skills, and strengthen the culture of reading as part of character development. The implementation of this project is supported by the concept of educational management which includes planning, organizing, implementing and evaluating. This project is expected to be replicated in other schools to support the school literacy movement (GLS) and the Merdeka Curriculum, in order to create a generation of independent and characterful learners.